Romane vs romanesque : a invenção de uma nomenclatura - Botelho, Maria Leonor (2018)
Assuming that only the knowledge of the evolution of ideas about a stylistic conceptallows us to understand entirely the thought about it, this communication aims to discuss thetime of the invention/adaptation the thought that it has, this communication seeks to discussthe moment of the invention/adaptation of the romanesque term internationally. e traditionalhistoriography on the subject has been focused exclusively on the role that France played inthis context, by imputing C. Gerville (1769-1853) the creation of the term romane (1818). ussupporting our discourse in the scientic work of two authors Tina W. Bizzaro (1992) and J.Nayrolles (2005) we will highlight the claim (and acceptance) the novelty of W. Gunn (1750-1841)in the invention romanesque word (1813). Recognizing the importance of this historiographicaldebate, we intend to discuss the dierent perspectives that have contributed substantially to thecreation of a historiographical rupture by recognizing the specicities of the romanesque in itsdierent dimensions.